INTENTION TO PLAY E-SPORTS AMONG UNIVERSITY STUDENTS - Yusri Abdullah; Siti Nurfarliana Mohd Yusof; Rossetty Dolly Anak Cheliku; Wu Yue (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Filling the void from advancements in technology and internet availability, university students are newly discovering online sports. This study aims to ascertain the elements that affect e-sports intention, specifically enjoyment, escapism and social interaction. A validated structured questionnaire using Google Forms was distributed to 51 individuals in the e-sports community at Universiti Pendidikan Sultan Idris (UPSI). Frequency and percentages as descriptive statistics were utilized in SPSS software for data analysis. The findings reveal that participants engage in e-sports mainly because of their enjoyment and social interaction, with lesser emphasis on escapism. The findings shows that student e-sport intention was more focused into both gaming and watching live-streamed games. Through the research, we will understand psychological well-being and risks in E-sports that will help develop preventive interventions for educational institutions to promote responsible gaming. This implies to governors of learning institutions, those who make laws for education and other sectors, and people who participate in electronic sports that e-sports need to be taken seriously as a significant and attractive feature.